The changing meaning of Taylagan Festival for contemporary Russia Buryat society: An adaptation of tradition - Rania Ayu Shila Febriani Adari; Mina Elfira (Universitas Trunojoyo Madura, 2021)
Festival is a product of a culture that develops according to the needs and times, including the Taylagan Festival. Taylagan Festival is one of the most important annual rituals for the Russian Buryat Shamans. In the contemporary era, this festival has also been performed for tourists. By using Roland Barthes’s semiotic theory, this research explores the impact of the changes of Taylagan Festival meanings for Russian Buryat contemporary society. At the same time, Eric Hobsbawm’s “The Invention of Tradition